MAPPING POTENTIAL TECHNOLOGY APPROPRIATE SMALL AND MEDIUM ENTERPRISES AS EFFORTS TO IMPROVE TECHNOLOGY PREPARATION LEADERSHIP IN REGION OF PONOROGO - Rochmat Aldy Purnomo; Titin Eka Ardiana (MediaTrend, 2017)
Research Objectives "Mapping the Potential of Appropriate Technology for Small and Medium Enterprises as an Effort to Improve the Capability of Technology Readiness in Ponorogo District" is to describe the profile of small and medium enterprises (SMEs), evaluate and measure the level of technological readiness ability (TK2T) of SMEs in Ponorogo District. The analytical tool used is a technometer that serves to measure the level of technological readiness capability used for the production of SMEs divided into three stages, basic (level 1 to level 3), medium (level 4 to level 6) and ready (Level 7 to With Level 9). By using teknometer is expected to provide basic information about mapping the potential needs and the use of appropriate technology (TTG) both tools, processes and production results in Ponorogo regency. SMEs in Ponorogo Regency are dominated in the field of food, handicraft and textile fields. The SME food business unit still requires major government intervention on production process issues. The majority of SMEs business unit in the field of food still use technology (tools) simple and potluck. The production process of SMEs business still neglects the hygienic side of both the production and production. The results of the evaluation and measurement of SME TK2T in Ponorogo District indicate that all samples have passed measurements at level 1 to level 3. Less than 50% pass the middle level ie level 4 to level 6, while less than 10% have passed the top level measurement , Which is level 7 to level 9. This explains that the production of SMEs in Ponorogo Regency still need government intervention both in the use of appropriate technology, as well as supporting indicators such as management, hygiene in production, human resources.